How do college students form expectations? - Basit Zafir (Federal Reserve Bank of New York, 2009)
Because students rely on their subjective expectations when choosing a college major, understanding this process of expectations formation is crucial for education policy recommendations. This paper focuses on how college students form expectations about various major-specific outcomes. I collect a unique panel data set of Northwestern University undergraduates that contains their subjective expectations about major-specific outcomes. Although students tend to be overconfident about their future academic performance, I find that they revise their expectations about various major-specific outcomes in systematic ways. For example, students who receive extremely positive information about their ability revise upward their prediction for short-term grade-point average (GPA). Similarly, those who receive very negative information revise downward their beliefs about GPA. Furthermore, students seem to update their probabilistic beliefs in a manner consistent with Bayesian analysis: Prior beliefs about outcomes to be realized in college tend to be fairly precise, while new information influences prior beliefs about outcomes in the workplace. Moreover, students who are more uncertain about major-specific outcomes in the initial survey make greater absolute revisions in their beliefs in the follow-up survey. Finally, I present evidence that learning plays a role in the decision to switch majors. Negative revisions to beliefs about graduating in four years, enjoying coursework, and earning an expected salary are associated with dropping a major.
Keywords: D8; I2; J1; J7; 330; College majors; learning; expectations